SOCIAL INCLUSION OF FORCEDLY DISPLACED PERSONS THROUGH TOURIST ACTIVITIES IN THE CONDITIONS OF THE RUSSIAN-UKRAINIAN WAR - Chvertko , L. A.; Kyryliuk , I. M. (The actual problems of regional economy development, 2023)
The article is aimed at the study of social inclusion forced displaced persons by means of tourist activity in the conditions of the Russian-Ukrainian war. The full-scale armed attack of Russia on Ukraine caused the forced migration of the Ukrainian population both within the country and beyond. For the most part, displaced persons are in a state of social exclusion and need social support from the state and civil society. The purpose of the study is to substantiate ways to ensure the social inclusion of forced displaced persons by means of tourist activity in the conditions of the large-scale Russian invasion of Ukraine. The study used dialectical and abstract-logical methods, methods of systematic approach, comparison, observation, analysis, synthesis, induction, deduction, etc. The article states that as a result of hostilities in the territory of Ukraine for forcibly displaced persons who have fallen into difficult life circumstances, it is important to be included in a new social environment and restorative psycho-emotional state. Accordingly, the task of both international and national governmental and non -governmental organizations is to develop measures aimed at social inclusion and adaptation of displaced persons. It is determined that social adaptation and social inclusion are forced on displaced persons through the use of various methods and technologies, among which a special place belongs to tourist activity. The Ukrainian and Polish experience of organizing and conducting various tourist activities for forced migrants is considered. It is substantiated that the practice of using excursion walks, thematic excursions, festivals, and workshops contributes to improving the quality of life forced persons. Integration spaces created in the territory of the community communities open up new opportunities for mutual assistance, form a friendly environment, and provide non-conflict integration and social inclusion. It has been proven that the organization of tourist activities with the involvement of psychologists, teachers, social workers, etc., is now being proven to ensure the social inclusion of displaced persons in a new habitat of widespread use. This contributes not only to the formation of a positive emotional climate and the acquaintance of forced migrants with the culture and traditions of the region or the country that accepts them but also to acquire new skills and developing their new internal qualities.